The effects of brief cognitive behaviour therapy for depression and homesickness among international students in Malaysia - Coumaravelou, Saravanan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Students who go to other countries for higher education face various psychological problems. Homesickness and depression are considered as major problems associated with this transition. The objectives of the experimental study are: (a) to identify the prevalence of depression and homesickness among international students; (b) to identify whether students receive brief cognitive behaviour individual therapy for depression reduces the level of homesickness between pre, post and follow-up assessment; and (c) to identify differences among scores of participants experience only homesickness and scores of homesickness with depression among international students. Some international students overcome and manage their homesickness and depression without taking brief cognitive behaviour individual therapy. In order to support and explore the results of the experimental data, the present study used qualitative method to identify the positive self-help coping strategies used by international students to manage their symptoms of depression and feelings of homesickness in Malaysia. The sample consisted of 520 first year undergraduate international students. The experimental group's students who were diagnosed with depression and homesickness received seven sessions of brief cognitive behaviour individual therapy for depression to reduce homesickness, the control group's students who were diagnosed with depression and homesickness received one session of advice and suggestions and the comparison group's students who experienced only homesickness did not receive any interventions. The present study used the comparison group to find out the interaction effect between students experiencing only homesickness and students experiencing both homesickness and depression. Results indicate that students who received brief cognitive behaviour individual therapy showed a significant reduction in their scores on homesickness and depression compared to the scores of students in the control group. Students who experienced only homesickness exhibited significant reduction in the scores on homesickness in the post-assessment compared to the control group's post-assessment scores on homesickness. Results of the qualitative study show that international students used various positive self-help coping strategies such as sharing their problems with others, getting themselves busy with some useful activities, doing physical exercise, facing the situation courageously, thinking positively about themselves and the future, and indulging in religious activities to overcome their homesickness and depression. Overall, brief cognitive behaviour individual therapy for depression and positive self-help coping strategies are effective to overcome homesickness and depression among international students.